Connect with experts and get insightful answers on IDNLearn.com. Our Q&A platform offers detailed and trustworthy answers to ensure you have the information you need.
Sagot :
To find the other root of the quadratic equation [tex]\(x^2 - 4x + 3 = 0\)[/tex] given that one root is 1, we can use the properties of quadratic equations and the relationships between their roots and coefficients.
A quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex] has roots that satisfy the following properties:
1. The sum of the roots ([tex]\(r_1 + r_2\)[/tex]) is given by [tex]\(-\frac{b}{a}\)[/tex].
2. The product of the roots ([tex]\(r_1 \cdot r_2\)[/tex]) is given by [tex]\(\frac{c}{a}\)[/tex].
Given equation: [tex]\(x^2 - 4x + 3 = 0\)[/tex]
Here:
[tex]\(a = 1\)[/tex]
[tex]\(b = -4\)[/tex]
[tex]\(c = 3\)[/tex]
We are given that one root, [tex]\(r_1\)[/tex], is [tex]\(1\)[/tex]. We need to find the other root, [tex]\(r_2\)[/tex].
1. Sum of the Roots:
The sum of the roots is:
[tex]\[ r_1 + r_2 = -\frac{b}{a} = -\frac{-4}{1} = 4 \][/tex]
Since [tex]\(r_1 = 1\)[/tex]:
[tex]\[ 1 + r_2 = 4 \][/tex]
Solving for [tex]\(r_2\)[/tex]:
[tex]\[ r_2 = 4 - 1 \][/tex]
[tex]\[ r_2 = 3 \][/tex]
2. Verification with Product of the Roots:
The product of the roots is:
[tex]\[ r_1 \cdot r_2 = \frac{c}{a} = \frac{3}{1} = 3 \][/tex]
Substituting [tex]\(r_1 = 1\)[/tex] and [tex]\(r_2 = 3\)[/tex]:
[tex]\[ 1 \cdot 3 = 3 \][/tex]
Since the product of [tex]\(1\)[/tex] and [tex]\(3\)[/tex] equals [tex]\(3\)[/tex], our calculated root [tex]\(r_2 = 3\)[/tex] satisfies both the sum and product properties.
Thus, the other root of the quadratic equation [tex]\(x^2 - 4x + 3 = 0\)[/tex] is:
[tex]\[ \boxed{3} \][/tex]
So, the correct answer is:
(C) 3
A quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex] has roots that satisfy the following properties:
1. The sum of the roots ([tex]\(r_1 + r_2\)[/tex]) is given by [tex]\(-\frac{b}{a}\)[/tex].
2. The product of the roots ([tex]\(r_1 \cdot r_2\)[/tex]) is given by [tex]\(\frac{c}{a}\)[/tex].
Given equation: [tex]\(x^2 - 4x + 3 = 0\)[/tex]
Here:
[tex]\(a = 1\)[/tex]
[tex]\(b = -4\)[/tex]
[tex]\(c = 3\)[/tex]
We are given that one root, [tex]\(r_1\)[/tex], is [tex]\(1\)[/tex]. We need to find the other root, [tex]\(r_2\)[/tex].
1. Sum of the Roots:
The sum of the roots is:
[tex]\[ r_1 + r_2 = -\frac{b}{a} = -\frac{-4}{1} = 4 \][/tex]
Since [tex]\(r_1 = 1\)[/tex]:
[tex]\[ 1 + r_2 = 4 \][/tex]
Solving for [tex]\(r_2\)[/tex]:
[tex]\[ r_2 = 4 - 1 \][/tex]
[tex]\[ r_2 = 3 \][/tex]
2. Verification with Product of the Roots:
The product of the roots is:
[tex]\[ r_1 \cdot r_2 = \frac{c}{a} = \frac{3}{1} = 3 \][/tex]
Substituting [tex]\(r_1 = 1\)[/tex] and [tex]\(r_2 = 3\)[/tex]:
[tex]\[ 1 \cdot 3 = 3 \][/tex]
Since the product of [tex]\(1\)[/tex] and [tex]\(3\)[/tex] equals [tex]\(3\)[/tex], our calculated root [tex]\(r_2 = 3\)[/tex] satisfies both the sum and product properties.
Thus, the other root of the quadratic equation [tex]\(x^2 - 4x + 3 = 0\)[/tex] is:
[tex]\[ \boxed{3} \][/tex]
So, the correct answer is:
(C) 3
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Find precise solutions at IDNLearn.com. Thank you for trusting us with your queries, and we hope to see you again.